Eat less or exercise more? Our intuitive theories and the burden of weight - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2018)
Our nave beliefs about what we choose to implicate as the cause of excess weight have immense influence on what we choose to consume and how much.